2023
DOI: 10.1002/acr2.11590
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Lupus and the Role of Social Determinants of Health: Current State of Knowledge and Directions for Future Research

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. The complex relationships between race and ethnicity and social determinants of health (SDOH) in influencing SLE and its course are increasingly appreciated. Multiple SDOH have been strongly associated with lupus incidence and outcomes and contribute to health disparities in lupus. Measures of socioeconomic status, including economic instability, poverty, unemployment, and food insecurity, as well as features of the neighborhood and built envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 106 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…These can exacerbate existing disparities in marginalised and underserved populations and violate the bioethical principles of justice. SLE is a disease that disproportionately affects racial and ethnic minorities and is therefore more sensitive to these issues (reviewed in ref 175 ). The lack of representation by minority populations in clinical research, genetic reports 176 and clinical trials 177 is a real concern.…”
Section: Future Considerationsmentioning
confidence: 99%
“…These can exacerbate existing disparities in marginalised and underserved populations and violate the bioethical principles of justice. SLE is a disease that disproportionately affects racial and ethnic minorities and is therefore more sensitive to these issues (reviewed in ref 175 ). The lack of representation by minority populations in clinical research, genetic reports 176 and clinical trials 177 is a real concern.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Despite immense disparities in systemic lupus erythematosus (SLE) care for racial and ethnic minorities [ 17 ], there remains a paucity of PN programs serving those suffering from rheumatological diseases. Some studies, however, have shown efficacy of PN interventions in this population.…”
Section: Introductionmentioning
confidence: 99%